Modern look to the risk factors and prevention of cervical cancer - A. I. Rybin (Kazimierz Wielki University, 2020)
An analytical review of research in the field of epidemiology and carcinogenesis of cervical cancer and measures and technologies for the prevention of this form of cancer has been carried out. There are considered data on the main proven risk factors for cervical cancer, which are as follows: certain characteristics of sexual behavior and reproductive history, sexual infections and infection with human papillomavirus (HPV), tobacco smoking and some other lifestyle characteristics. According to world reference data the analysis of existing methods of cervical cancer prevention including sanitation, HPV vaccination and various types of screening for cervical cancer was conducted. Data on the significance, effectiveness and availability of various preventive technologies are presented.